Reactive multi-agent approach to local platoon control: stability analysis and experimentations. (25th May 2011) - Contet, Jean-Michel; Gechter, Franck; Gruer, Pablo; Koukam, Abderrafiaa
This paper presents a local control approach to linear platoons, systems of vehicles that displace together adopting a train configuration without any material coupling. Linear platoon technology is considered as a potential base for the definition of new urban transportation services. The main problems related to platoon systems is the geometry control: control of inter-vehicle distance and common trajectory matching. The geometry control problem is generally treated according to one of two approaches: global or local. This paper focuses on a local approach which does not require sophisticated sensors and/or costly road equipment. The objective of this local control approach allows satisfactory distance regulation and matching to any common trajectory, by using local perception capabilities of platoon's vehicles. The basic perception capability consists in measuring the vectorial distance between a given vehicle and its predecessor. The behaviour of each platoon vehicle is determined by a physics inspired interaction model based on a virtual spring-damper. Stability and other platoon safety properties are analysed on the base of the physics inspired interaction model. Both simulation and experimentation have been used to measure trajectory error and to evaluate inter-vehicle distance during platoon evolution.